2019
DOI: 10.1542/neo.20-3-e135
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance in the Neonatal Intensive Care Unit

Abstract: Antibiotic-resistant bacteria are an increasing problem in the NICU. Ineffective empiric antibiotic therapy is associated with increased risk for morbidity and mortality. Organisms that are resistant to multiple antimicrobial agents (multidrug-resistant organisms) are particularly problematic. These organisms may be transmitted to infants if infection control practices are not adhered to, or they may be created by antibiotic exposure. Therefore, meticulous infection prevention—including hand hygiene, surveilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 44 publications
0
13
0
1
Order By: Relevance
“…This may be explained by the lower frequency of hospital admission and/or lower consumption of antibiotics among children and adolescents in Europe compared to other age groups [44]. Increasing VREFm proportions in infants not neonates and elderly patients is of concern since ineffective antibiotic therapies are associated with increased mortality and morbidity in these vulnerable patient groups [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the lower frequency of hospital admission and/or lower consumption of antibiotics among children and adolescents in Europe compared to other age groups [44]. Increasing VREFm proportions in infants not neonates and elderly patients is of concern since ineffective antibiotic therapies are associated with increased mortality and morbidity in these vulnerable patient groups [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Authors suggest that this is driven by the high levels of ampicillin resistance and prohibition of gentamicin use due to the high risk of hearing loss in the population. Against this backdrop, the widespread availability and antimicrobial use in neonates and the contribution of antimicrobial resistance as a complicating factor in neonatal sepsis becomes extremely important and rather than increasing use of antibiotics, infection prevention measures such as hand hygiene, surveillance cultures, contact precautions and antibiotic stewardship should be implemented [86].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the ARGs identified in this study are known to be present in potentially pathogenic bacterial species, including Klebsiella and Enterobacter spp., which are responsible for nosocomial infections as well as more severe morbidities including NEC [52,K 53] and late-onset sepsis [52,K 53]. In addition, we detected unique ARG signatures transferred to infants, and were able to observe the rapid acquisition of site-specific ARGs, which highlights the NICU environment as a source of antibiotic resistance microbes that can be transferred between NICUs [54]. We also found that infants acquire these ARGs throughout their NICU stay, suggesting that reducing hospitalization times may limit the acquisition of nosocomially acquired antibiotic-resistant bacteria.…”
Section: Discussionmentioning
confidence: 86%